IDeglira vs insulin degludec for type 2 diabetes: a systematic review and meta-analysis - Liu, Yang; Li, Xuejing; Yang, Jie; Qie, Suhui; Wang, Xiaoli; Wang, Xianying; Zheng, Yingying (Frontiers in Endocrinology, 2025)
ObjectivesThis systematic review and meta-analysis was to evaluate and compare the efficacy and safety profiles of IDegLira versus insulin degludec in the management of type 2 diabetes (T2D).MethodsA comprehensive search was systematically conducted across PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov from their inception until March 11, 2025. The search focused on randomized controlled trials (RCTs) that compared IDegLira with insulin degludec in adult patients with T2D. The primary outcomes of interest included change in glycated hemoglobin (HbA1c) and body weight. Random-effects meta-analyses were performed using RevMan 5.4 and Stata 16.0 software.ResultsA total of six eligible RCTs, encompassing 3,393 patients (2,075 receiving IDegLira and 1,318 receiving insulin degludec), were included in the analysis. Treatment with IDegLira resulted in significant reductions in HbA1c (MD -0.79%, 95%CI: -1.03% to -0.54%), body weight (MD -1.62 kg, 95% CI: -2.13 kg to -1.11 kg), fasting plasma glucose (MD -0.45 mmol/L, 95% CI: -0.77 mmol/L to -0.14 mmol/L), self-measured plasma glucose (MD -1.00 mmol/L, 95% CI: -1.42 mmol/L to -0.59 mmol/L), and systolic blood pressure (MD -2.23 mmHg, 95% CI: -3.63 mmHg to -0.82 mmHg). In comparison to insulin degludec, IDegLira demonstrated superior blood glucose control, as evidenced by a higher proportion of patients achieving HbA1c levels below 7.0% and 6.5%, as well as those achieving these targets without weight gain and severe or blood glucose-confirmed hypoglycemic episodes. Additionally, patients treated with IDegLira required significantly lower daily insulin doses. Notably, the risk of severe or blood glucose-confirmed symptomatic hypoglycemia, adverse events, and severe adverse events was comparable between IDegLira and insulin degludec.ConclusionsThis meta-analysis provides compelling evidence that IDegLira offers superior glycemic control and more favorable effects on body weight compared to insulin degludec, while maintaining a comparable safety profile.